Questions of resilience in municipal finance response to a shock event: a case study of the Cape Town drought - Cooke, Kayleen (Department of Civil Engineering, 2020)
The gaining prominence of resilience in urban policy has meant that urban decision makers are increasingly being asked to exhibit foresight and preparedness in how the urban system is planned and managed. The City of Cape Town has accepted this principle of resilience as a key means of driving collective understanding and action within the urban system in a time of growing uncertainty. Cape Town recently experienced the worst natural disaster in the history of its city-dom, in the form of a three-year drought. The impact of this drought on the municipal budget has been formidable. In terms of expenditure, considerable adjustments to the planned expenditure had to be made in order to source the funds required for large-scale infrastructure projects designed to increase resilience within the municipal water supply. In terms of revenue, there is significant concern around the fiscal sustainability of the municipality as more and more households are developing their own water supply in the form of rainwater tanks and boreholes, which is anticipated to decrease the municipal revenue gained from water tariffs dramatically (CCT, 2018f). The story of how the municipal budget system was affected by and reacted to the drought provides an opportunity to observe the application of the City’s understanding of resilience to a complex system, where many actors undertake simultaneous and independent activities, and the impact of these activities is evident at multiple levels and across multiple systems and sub-systems.